2011
DOI: 10.1002/pssc.201001054
|View full text |Cite
|
Sign up to set email alerts
|

Study of carrier dynamics and radiative efficiency in InGaN/GaN LEDs with Monte Carlo method

Abstract: In this paper, we have applied the Monte Carlo method to study carrier dynamics in InGaN quantum well. Vertical and lateral transport and its impact on device radiative efficiency is studied for different In compositions, dislocation densities, temperatures, and carrier densities. Our results show that the non‐radiative recombination caused by the defect trapping plays a dominating role for higher indium composition and this limits the internal quantum efficiency (IQE). For lower indium composition cases, carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…112,120,121 The prime requisite for a better understanding of experimental information is probably an improved description of carrier transport across the active region. Promising efforts are represented by momentum-resolved models 23,122 and analytic-band Monte Carlo (MC) transport simulations, 123 but the need for a full-band MC approach (FBMC, possibly integrated with microscopic models of radiative and nonradiative recombination processes) is apparent, especially after the recent debate following the proposed identification of Auger recombination as the dominant mechanism in droop from electron emission spectroscopy experiments, 124 where FBMC analysis has suggested that the LED structure under investigation was probably unsuitable to recover an Auger signature. 125 …”
Section: Discussionmentioning
confidence: 99%
“…112,120,121 The prime requisite for a better understanding of experimental information is probably an improved description of carrier transport across the active region. Promising efforts are represented by momentum-resolved models 23,122 and analytic-band Monte Carlo (MC) transport simulations, 123 but the need for a full-band MC approach (FBMC, possibly integrated with microscopic models of radiative and nonradiative recombination processes) is apparent, especially after the recent debate following the proposed identification of Auger recombination as the dominant mechanism in droop from electron emission spectroscopy experiments, 124 where FBMC analysis has suggested that the LED structure under investigation was probably unsuitable to recover an Auger signature. 125 …”
Section: Discussionmentioning
confidence: 99%
“…To create a conclusive and quantitative link between the droop, Auger recombination in the QWs and the hot electron emission at the semiconductor surface, one needs fully microscopic device-level simulations of non-equilibrium transport in realistic III-N LEDs, in addition to reliable models for Auger recombination and other scattering rates. With the exception of microscopic models restricted to carrier dynamics within the QWs, 6 earlier simulations have relied heavily on quasi-equilibrium models, e.g., the drift-diffusion (DD) model, 7-11 which do not account for hot electrons at high input powers. To describe hot electrons and to maintain computational feasibility, we have combined the MC and DD methods.…”
mentioning
confidence: 99%
“…However, the lattice mismatch between GaN and GaInN in conventional MQWs causes degradation of crystalline quality and the quantum-confined Stark effect (QCSE) . As the InN mole fraction of GaInN is increased, the above two effects become more pronounced. , In fact, it has been reported that the maximum internal quantum efficiency (IQE) in a planar (0001) plane LED with 10% InN mole fraction and a dislocation density of 10 8 cm –2 is approximately 60%, while the value decreases to 25% as the In composition increased to 20%. , Thus, GaInN-based LEDs have the problem of considerably low efficiency in the long-wavelength region . The second challenge is efficiency degradation caused by carrier overflow in the thin GaInN/GaN MQWs, and the structures with a thicker GaInN quantum well usually suffer from a tradeoff between preventing carrier overflow and suppressing QCSE.…”
Section: Introductionmentioning
confidence: 99%